PENDEKATAN GENDER DALAM ISLAM PERSPEKTIF SACHIKO MURATA - Afifah Afifah (Tarunaedu: Journal of Education and Learning, 2023)
Sachiko Murata in gender issues uses arguments based on the approach of the theory of the universe (cosmology) as the basis of his thinking and more towards the textual (mystical) with "entrust" to the interpretation of bi al-History (bi al-Ma'sur) or more known by theological concept. Gender is basically a social construct or a form of society. Where it has been established in the community that women are in charge of the domestic territory which covers the provisions of the role of caring, nurturing, passivity and receiving. While men have provisions of the opposite role. In many ways, gender stereotypes are still attached between men and women. Starting from here that then lead to discrimination against women. Because not all men are able to be assertive and can ngatur, then a gentle man will be branded a sissy, whereas if women are more daring and firmly will be branded a tomboy. Of course this is uncomfortable and stressful, whereas everyone is equal in the merits of a human being.